Two new species of the genus Ptycholaimellus Cobb, 1920 (Nematoda: Chromadoridae) from coastal zone of North Vietnam sea - Thanh, Nguyen Vu; Tu, Nguyen Dinh; G. Gagarin, Vladimir; V. Tchesunov, Alekcei; Hien, Nguyen Thanh (Academia Journal of Biology, 2013)
Two new marine nematode species of the family Chromadoridae collected from coastal zone of North Vietnam sea were described and illustrated are Ptycholaimellus brevisetosus sp. n. and Ptycholaimellus areniculus sp. n.. The new species P. brevisetosus sp. n. resembles to P. pandispiculatus (Hopper, 1961) but differs from it by the longer body, absence of somatic and cervical setae, more wide labial region, longer cephalic setae and longer spicules, and P. areniculus sp. n. resembles to P. macrodentatus (Timm, 1961) but differs from it by the longer body, relatively shorter cephalic setae, absence of knob-like swellings at base of dorsal tooth in stoma and presence of small piece in spicular apparatus of males.